Inorganic chemistry - House, J. E. (Academic Press, 2008)
Inorganic Chemistry provides essential information in the major areas of inorganic chemistry. The author emphasizes fundamental principles―including molecular structure, acid-base chemistry, coordination chemistry, ligand field theory, and solid state chemistry ― and presents topics in a clear, concise manne